2018
DOI: 10.1021/acs.jpcb.8b08766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquids as Cosurfactants on Photoinduced Electron Transfer in Tetronic Micelles

Abstract: This study investigates the role of varying alkyl chain lengths of a series of surface-active 1-alkyl-3-methylimidazolium tetrafluoroborate ([C n MIm]­[BF4], n = 4, 6, and 10) ionic liquids (ILs) as cosurfactants in modifying the micellar characteristics of a tetronic star-block copolymer, T1304, and the consequent effects on bimolecular photoinduced electron transfer (PET) reactions carried out in these T1304–IL mixed micellar systems. Using coumarin 153 as the probe dye and following ground-state absorption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Two distinct correlations can be observed at the lower and higher T904 concentration regions, with clear break points that correspond to the CMC (Table S1). The CMC values are found to decrease with either the increase in temperature at a given pH (8.5) or the increase in pH at a given temperature (30 °C) of the medium, in accordance with previous literature reports that high temperature and pH favor the formation of micelles in T904. ,, …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Two distinct correlations can be observed at the lower and higher T904 concentration regions, with clear break points that correspond to the CMC (Table S1). The CMC values are found to decrease with either the increase in temperature at a given pH (8.5) or the increase in pH at a given temperature (30 °C) of the medium, in accordance with previous literature reports that high temperature and pH favor the formation of micelles in T904. ,, …”
Section: Resultssupporting
confidence: 91%
“…For the present study, five different pH and temperature combinations were considered (pH 8.5, 30 °C; pH 8.5, 50 °C; pH 8.5, 20 °C; pH 10.0, 30 °C; and pH 6.0, 30 °C), to emulate the assembled (micelle) and dissociated (unimer) states of T904. The self-assembly behavior and CMC values under these conditions were monitored by the shift in the emission spectrum of the solvatochromic coumarin dye, C153, with increasing concentrations of the star block copolymer . As depicted in Figure , at pH 8.5, 30 °C; pH 8.5, 50 °C; and pH 10.0, 30 °C, there is initially a sharp decrease in the emission maximum (λ max ) of C153 with progressive addition of T904 to the aqueous solution of the dye, followed by a gradual decrease in λ max at higher concentrations of T904.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study evaluated the mechanical properties of PEEK composites synthesized using ILs, [BMIM] HSO 4 , and [EMIM]Ac (Figure S8) and discovered that [BMIM]HSO 4 -based PEEK composites exhibited better elastic modulus and tensile strength. This explanation was strengthened by earlier research in which several authors 48,49 demonstrated that ILs with a bigger alkyl chain might establish significant interactions with both the filler and polymer matrix, which was critical for improving the MWCNTs distribution and mechanical characteristics.…”
Section: Mechanical Behavior Of Peek/ Mwcnts Nanocompositesmentioning
confidence: 95%